(untitled) (Proceedings of the International Conference on Public Health, 2019)
The main objective was to determine the association between ergonomic mismatch and self-reported pain among students from a college in a public university in the Philippines. The prevalence of ergonomic mismatch, self-reported pain, and pain qualities were also determined. The dimensions of the representative Auditorium, Wood-and-Metal, and Plastic chairs were compared with the anthropometric measurements taken while the students were sitting on the chairs to assert mismatch. Self-administered questionnaires were used to determine self-reported pain and its quality per body part. Logistic regression was utilized to establish the presence of an association between ergonomic mismatch and self-reported pain while accounting for confounders. All students were mismatched with the Auditorium chair, 88.68% with the Wood-and-Metal chair, and 89.10% with the Plastic chair. Sitting Shoulder Height to Backrest Height and Hip Breadth to Seat Width contributed the highest mismatch for all three chairs, and the most prevalent pain was heaviness in the back and neck. Association was established for the Plastic and Wood-and-Metal chairs, with mismatched students 54% and 29% more likely experiencing pain than matched students, respectively. For the Auditorium chair, association was established with mildly mismatched students 60% more likely to experience pain than severely mismatched students.